A differential‐fed Yagi–Uda antenna with enhanced bandwidth via addition of parasitic resonator. Issue 1 (January 2017) - Luo, Yu; Chu, Qing‐Xin; Bornemann, Jens
ABSTRACT: A printed‐circuit differential‐fed Yagi–Uda antenna is presented that features enhanced bandwidth by employing a parasitic quarter‐wavelength coplanar stripline (CPS) resonator which adds one more resonant mode within the operating bandwidth. The proposed antenna is designed, fabricated and measured. Experimental results are in good agreement with simulations. In the band of 2.27–2.58 GHz, the return loss is better than 10 dB and the gain better than 6 dBi. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:156–159, 2017